Changes in Vedolizumab Utilization Across US Academic Centers and Community Practice Are Associated With Improved Effectiveness and Disease Outcomes. Issue 11 (3rd May 2019) - Koliani-Pace, Jenna L; Singh, Siddharth; Luo, Michelle; Hirten, Robert; Aniwan, Satimai; Kochhar, Gursimran; Chang, Shannon; Lukin, Dana; Gao, Youran; Bohm, Matthew; Swaminath, Arun; Gupta, Nitin; et al.
Abstract: Background: Vedolizumab effectiveness estimates immediately after Food and Drug Administration (FDA) approval for ulcerative colitis (UC) and Crohn's disease (CD) are limited by use in refractory populations. We aimed to compare treatment patterns and outcomes of vedolizumab in 2 time frames after FDA approval. Methods: We used 2 data sets for time trend analysis, an academic multicenter vedolizumab consortium (VICTORY) and the Truven MarketScan database, and 2 time periods, May 2014–June 2015 (Era 1) and July 2015–June 2017 (Era 2). VICTORY cumulative 12-month clinical remission, corticosteroid-free remission, and mucosal healing rates, and Truven 12-month hospitalization and surgery rates, were compared between Eras 1 and 2 using time-to-event analyses. Results: A total of 3661 vedolizumab-treated patients were included (n = 1087 VICTORY, n = 2574 Truven). In both cohorts, CD and UC patients treated during Era 2 were more likely to be biologic naïve. Compared with Era 1, Era 2 CD patients in the VICTORY consortium had higher rates of clinical remission (31% vs 40%, P = 0.03) and mucosal healing (42% vs 58%, P < 0.01). These trends were not observed for UC. In the Truven database, UC patients treated during Era 2 had lower rates of inflammatory bowel disease–related hospitalization (22.4% vs 9.6%, P < 0.001) and surgery (17.2% vs 9.4%, P = 0.008), which was not observed for CD. Conclusion: Since FDA approval, remission and mucosal healing rates have increased for vedolizumab-treated CD patients, and vedolizumab-treated UC patients have had fewer hospitalizations and surgeries. This is likely due to differences between patient populations treated immediately after drug approval and those treated later. Abstract : There has been a shift in utilization of vedolizumab in both Crohn's disease and ulcerative colitis toward earlier use in the treatment sequencing algorithm. This shift in utilization is associated with improvements in response and disease outcomes.